Dog food production using curcumin as antioxidant: effects of intake on animal growth, health and feed conservation - Campigotto G.* (2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.The objectives of this study were to produce dog food containing curcumin replacing synthetic antioxidants, to evaluate its beneficial effects on animal growth and health. Curcumin (100 mg/kg) was added after the extrusion process along with the other micronutrients. The final concentration of curcumin was 32.9 mg/kg. The control feed was composed of the same ingredients without curcumin. After a storage of 6 months, feed composition and pH did not differ; however, the feed with curcumin showed lower protein oxidation, lipid peroxidation and higher total antioxidant capacity. After 2 months of feed production, 12 young Beagle dogs received either curcumin-containing food (n = 6) or the control diet (n = 6). The animals were fed twice a day using individual kennels. Blood samples were taken on d 1, 35 and 42. During the first 30 d of the study, the animals had natural infectious diseases that were controlled with anti-protozoals and antibiotics. Greater numbers of red blood cells were observed in dogs fed with curcumin (d 35 and 45), and there were greater numbers of white blood cells as a consequence of increased neutrophils on d 42. At the end of the experiment, a significant reduction in the number of lymphocytes was observed in dogs that ingested curcumin (d 42), suggesting an anti-inflammatory effect, manifested as a decrease in globulin levels. In the final 15 d of the experiment, the animals were clinical healthy. Higher serum levels of glucose, urea, triglycerides and cholesterol were observed in dogs fed with curcumin. Curcumin increased the activity of several antioxidant enzymes in addition to non-protein thiols and the total antioxidant capacity in the serum, consequently reducing levels of oxygen reactive species. Curcumin supplementation of dogs did not favour growth or weight gain. Neverthless, it was concluded that curcumin improved animal health, with emphasis on the stimulation of the antioxidant system and evidence of an anti-inflammatory effect.